Achieving Presence through Evoked Reality - Pillai, Jayesh S.; Schmidt, Colin; Richir, Simon (Frontiers in Psychology, 2013)
The sense of ‘Presence’ (evolving from ‘telepresence’) has always been associated with virtual reality research and is still an exceptionally mystifying constituent. Now the study of presence clearly spans over various disciplines associated with cognition. This paper attempts to put forth a concept that argues that it’s an experience of an 'Evoked Reality’ (illusion of reality) that triggers an ‘Evoked Presence’ (sense of presence) in our minds. A Three Pole Reality Model is proposed to explain this phenomenon. The poles range from Dream Reality to Simulated Reality with Primary (Physical) Reality at the center. To demonstrate the relationship between Evoked Reality and Evoked Presence, a Reality-Presence Map is developed. We believe that this concept of Evoked Reality and the proposed model may have significant applications in the study of presence, and in exploring the possibilities of not just virtual reality but also what we call ‘reality’.